191k views
2 votes
Write the given expression as the tangent of an angle tan 3x-tan 7x/1+tan3x tan7x

tan(10x)
tan(8x)
tan(3x)
tan(-4x)
tan(-2x)

1 Answer

0 votes

\bf tan({{ \alpha}} + {{ \beta}}) = \cfrac{tan({{ \alpha}})+ tan({{ \beta}})}{1- tan({{ \alpha}})tan({{ \beta}})}\qquad tan({{ \alpha}} - {{ \beta}}) = \cfrac{tan({{ \alpha}})- tan({{ \beta}})}{1+ tan({{ \alpha}})tan({{ \beta}})}\\\\ -----------------------------\\\\ \cfrac{tan(3x)-tan(7x)}{1+tan(3x)tan(7x)}\implies tan(3x-7x)\implies tan(10x)
User AntonK
by
6.0k points